Nondiffusive Pitch‐Angle Scattering of a Distribution of Energetic Particles by Coherent Whistler Waves. Issue 6 (17th June 2020) - Yoon, Young Dae; Bellan, Paul M.
Abstract: Whether or not coherent magnetospheric whistler waves play important roles in the pitch‐angle scattering of energetic particles is a crucial question in magnetospheric physics. The interaction of a thermal distribution of energetic particles with coherent whistler waves is thus investigated. The distribution is prescribed by the Maxwell‐Jüttner distribution, which is a relativistic generalization of the Maxwell‐Boltzmann distribution. Coherent whistler waves are modeled by circularly polarized waves propagating parallel to the background magnetic field. It is shown that for parameters relevant to magnetospheric chorus, a significant fraction (1–5%) of the energetic particle population undergoes drastic, nondiffusive pitch‐angle scattering by coherent chorus. The scaling of this fraction with the wave amplitude may also explain the association of relativistic microbursts to large‐amplitude chorus. A much improved condition for large pitch‐angle scattering is presented that is related to, but may or may not include the exact resonance condition depending on the particle's initial conditions. The theory reveals a critical mechanism not contained in the widely used second‐order trapping theory. Plain Language Summary: A certain class of plasma waves called whistler waves is abundant in the Earth's magnetosphere. The interaction between whistler waves and energetic particles trapped in the Earth's magnetic field can cause the particles to escape the trap and cause pulsating auroras or damage spacecraft. Although previous studies have mostly focused on diffusive mechanisms, we show that a significant fraction of the energetic particles interacts nondiffusively or coherently with the wave. We also show that a widely used condition for such interaction is incomplete and provide a more accurate alternative. Key Points: A much improved condition is provided for how coherent whistler waves scatter the pitch‐angle of energetic particles A significant fraction of energetic, thermally distributed particles undergoes this scattering The theory reveals a critical mechanism not contained in the widely used second‐order trapping theory